Outcomes following total Laryngectomy for Squamous Cell Carcinoma at a Singapore Tertiary Referral Centre - Wei Zhong Ernest Fu; Ming Yann Lim; Jeevendra Kanagalingam; Christopher GL Hobbs (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Objectives: To evaluate the clinical outcomes and complications following total laryngectomy in a South-East Asian Population.  Design: 10-year retrospective review of cases of total laryngectomy or laryngo-pharygectomy.  Main  outcome measures: 5-year overall survival (OS) and disease-free survival (DFS). Results: 61 patients of which 55 (90%) had laryngeal SCC while 6 (10%) had hypopharyngeal SCC. Overall  edian survival was 85 months. 5-year OS and DFS for laryngeal SCC were 65% and 47%  respectively while 5-year OS and DFS for hypopharyngeal SCC were both 33%. Most common cause of  death was due to advanced cancer secondary to disease recurrence. Conclusion: Although there is increasing tendency towards laryngeal preservation, surgery remains a safe treatment option for selected patients with laryngeal and hypopharyngeal SCC. In our local population,  patients often present late with advanced cancer, as demonstrated by the high rate of emergency reoperative tracheostomy. However, there is no evidence that this affects survival.